PENGARUH PENGGUNAAN WEBSITE GAME INTERAKTIF TERHADAP PERKEMBANGAN KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN - Stefany Yunita Putri; Nurhafizah (STKIP Subang, 2025)
This article is written based on research conducted with the background of lowchildren's numeracy skills and the lack of variation in learning media that makeschildren quickly bored and less motivated. To overcome this, an interactive gamewebsite is used as an alternative learning media that is fun and interesting withoutdownloading the application first. The purpose of this study was to determine theeffect of using an interactive game website on childrens numeracy skills at TelkomSchools Padang Kindergarten. This study uses a quantitative approach with aquasi-experimental method. Samples were taken by purposive sampling, namelyclass B6 as the experimental group and B7 as the control group, each consistingof 18 children. Data were collected through oral tests and action tests, thenanalyzed using normality, homogeneity, and hypothesis tests with the help ofSPSS 25.0. The results showed that the average numeracy score of theexperimental class increased from 7.33 (pre-test) to 18.28 (post-test), while thecontrol class increased from 6.44 to 12.17. A significance value of 0.00 < 0.05indicates a significant effect. Thus, the use of interactive game websites hasproven effective in improving childrens numeracy skills at Telkom Schools PadangKindergarten.